Clinical and molecular characteristics of community‐acquired methicillin‐resistant Staphylococcus aureus infections in Chinese neonates. Issue 1 (6th August 2014) - Li, Shipeng; Ning, Xue; Song, Wenqi; Dong, Fang; Zheng, Yaojie; Chen, Qiang; Qiao, Yanhong; Li, Juan; Wang, Lijuan; Wang, Qun; Yue, Liqin; Wang, Aihua; et al.
<x xml:space="preserve">Abstract</x> This study aims to characterize the clinical features of community‐acquired methicillin‐resistant Staphylococcus aureus (CA‐MRSA) infections in Chinese neonates, as well as the molecular characteristics and expression of key virulence genes of isolates. Clinical information and molecular characteristics of 130 cases were analyzed. Up to 83.8% patients were affected with late‐onset infection. Cesarean delivery was the main delivery route, accounting for 74.6% of the total deliveries. Pneumonia (69, 53.1%) was the most common infection. A total of 38 patients (29.2%) suffered from complications. Moreover, 35 cases (26.9%) were invasive infections, among which 88.6% involved multiple organs and 45.7% suffered from complications. Cesarean section and premature birth were the risk factors for invasive CA‐MRSA infection. ST59‐MRSA‐SCCmecIVa‐t437 (54, 41.5%) was the most predominant CA‐MRSA clone. The hla expression in the ST59 isolates was higher than that in ST910 (p = 0.02) and the hla expression in ST59‐SCCmecV‐t437 was higher than that in ST59‐SCCmecIVa‐t437. Approximately, 46.4% (13/28) of the infections caused by ST59‐SCCmecV were invasive. This value is higher than that of ST59‐SCCmecVa caused infections (14/59, 23.7%) (p = 0.03). This study showed that neonatal CA‐MRSA infections in China readily become invasive, involve multiple organs, and are often accompanied by complications. The SCCmec V clone may be more pathogenic than the SCCmecVIa clone.